If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11f + 2(f + 1) = 5f + -6 Reorder the terms: 11f + 2(1 + f) = 5f + -6 11f + (1 * 2 + f * 2) = 5f + -6 11f + (2 + 2f) = 5f + -6 Reorder the terms: 2 + 11f + 2f = 5f + -6 Combine like terms: 11f + 2f = 13f 2 + 13f = 5f + -6 Reorder the terms: 2 + 13f = -6 + 5f Solving 2 + 13f = -6 + 5f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-5f' to each side of the equation. 2 + 13f + -5f = -6 + 5f + -5f Combine like terms: 13f + -5f = 8f 2 + 8f = -6 + 5f + -5f Combine like terms: 5f + -5f = 0 2 + 8f = -6 + 0 2 + 8f = -6 Add '-2' to each side of the equation. 2 + -2 + 8f = -6 + -2 Combine like terms: 2 + -2 = 0 0 + 8f = -6 + -2 8f = -6 + -2 Combine like terms: -6 + -2 = -8 8f = -8 Divide each side by '8'. f = -1 Simplifying f = -1
| 2(x+60)-((x+50)+60)=210 | | 29x=29x | | 100=4x+3y+0.1z | | -4p+4(1+2p)=-38-3p | | x^4+3x^3+3x^2+3x=0 | | 5x^2+3x-2y^2-3y-1=0 | | -4-(13x+6)+17=2+x-(14x-5) | | -4-(13x+6)+17=2 | | 9(3n+2)=8(8n+1)+8 | | 0=8x^2-42x+45 | | 5x+7=12-x | | -5u^2+21u+20=0 | | 2(6a-1)-(2a-3)+3(7a-5)= | | -6(7x-6)+3=-42x+39 | | -3(1-2x)=15 | | 6x+9=12x-15 | | -6(7x-6)+3=42x+39 | | S(t)=5t^3-2t^2+9 | | 85y=12(7y+33) | | X^6+x^3-6x=0 | | 7(x-2)-3(2x-7)=6x+22 | | -6(x-3)-29=-11 | | 8y-16y=-39-49 | | -10(x+5)+62=19-19 | | 5(b-1)=-13+5b | | -2(x-4)-4(-3x+5)=8 | | 42=0.8x+6 | | -2x+7=5-(7x+7) | | 37-3b=-2(1+8b) | | 3+2x=24 | | z^3+4z^2-64z-256=0 | | -y^2-25y+45=0 |